If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y + -10 + -1c = z Reorder the terms: -10 + Y + -1c = z Solving -10 + Y + -1c = z Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '10' to each side of the equation. -10 + Y + 10 + -1c = 10 + z Reorder the terms: -10 + 10 + Y + -1c = 10 + z Combine like terms: -10 + 10 = 0 0 + Y + -1c = 10 + z Y + -1c = 10 + z Add 'c' to each side of the equation. Y + -1c + c = 10 + c + z Combine like terms: -1c + c = 0 Y + 0 = 10 + c + z Y = 10 + c + z Simplifying Y = 10 + c + z
| 12t-52=-16 | | -5f-3+2t=24 | | 5x-9=-3y | | 3gh=f | | 2x+39=3x+18 | | 4x^2+70x+90=0 | | 9x=8-5(x-2) | | Y=X^2-10x-3 | | 98=(7x+1)+(2x+7) | | 3(x^2)=18 | | 8t-11=3t+14 | | 9x+5+5=15 | | 9y-8=2y+13 | | (8x+6)-(3x-4)= | | 5p-4=3p+18 | | 5p-15=2p+12 | | 15x^2=24 | | (8x+2)-(3x-4)= | | 14t-8=12t+18 | | 2x^2+36x-360=0 | | -4y+2x=2 | | og(10-4x)=log(10-3x) | | 21-5r=3(7r-3)+4 | | Yy=-6x+15 | | 4(x-5)=11 | | 30=13w-8w | | 3(5x-4)=13 | | 13.34-12.3u=5.54-12.7u | | xy+7=2a-8 | | 4x+5=0.6 | | 7x+9=7x+6 | | 8(3x-5)=8 |